2001
DOI: 10.1659/0276-4741(2001)021[0184:iolual]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Land Use and Land Cover Dynamics for Mountain Resource Degradation in the Northwestern Ethiopian Highlands

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
211
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(253 citation statements)
references
References 2 publications
19
211
2
2
Order By: Relevance
“…where β is vector of parameters of the model, X j is vector of explanatory variables, and ε j is the error term assumed to have random normal distribution with mean zero and common variance δ 2 [2]. I j = Unobservable (latent variable) households' actual decision to use SLM practice and what we observe is a dummy variable (use of land management measures) which is defined as: 1 if I j * > 0 and 0 otherwise…”
Section: Specification Of the Probit Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…where β is vector of parameters of the model, X j is vector of explanatory variables, and ε j is the error term assumed to have random normal distribution with mean zero and common variance δ 2 [2]. I j = Unobservable (latent variable) households' actual decision to use SLM practice and what we observe is a dummy variable (use of land management measures) which is defined as: 1 if I j * > 0 and 0 otherwise…”
Section: Specification Of the Probit Modelmentioning
confidence: 99%
“…In this type of economies, land degradation poses major development challenge contributing to reduced output, lower economic growth and increased poverty [1,2]. In recent years, this challenge is more aggravated in the face of changing climate and variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deforestation rates in East Africa, including Ethiopia, were the second highest in Africa: 0.94% for 1990-2000 and 0.97% for 2000-2005 [11]. A study conducted in North Western Ethiopia indicated 99% clearing of the forest cover of the 1950s until the year 1995 [12]. The population of Ethiopia, which is currently 79 million people, increases by almost two million annually under highly unfavorable economic and environmental conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the topography of the catchment as the source locations of the Upper Blue Nile River is dominated by rugged and mountainous landscapes. As a result of this, the catchment has been described previously as prone to soil erosion and gully formation [59,60], which has led to a (moderate) decline in soil fertility and loss of fertile plots for local farmers [61,62]. The continuing decline of grasslands and natural vegetation, combined with expanding cultivation, would imply that the local erosion and gully formation phenomenon is bound to deteriorate unless more effective policies and management interventions are developed and implemented.…”
Section: Model Evaluationmentioning
confidence: 99%